Wages, government policy and unemployment - Wilkinson, F; Michie, J (Edward Arnold, 1995)
In this paper we question the usefulness of what has become the new textbook orthodoxy — the 'new Keynesian' NAIRU theory. We then discuss the impact of the policy developments that follow from this orthodoxy, and argue that NAIRU theory has resulted in greater, not reduced, unemployment. Consequently, orthodox economic theory has added an upward twist to the stagnationist, high-unemployment ratchet.